2017
DOI: 10.21608/ejrs.2017.46575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rosemary and Marjoram Supplementation on Growth Performance, Digestibility and Economic Efficiency of Growing Rabbits

Abstract: This study was conducted to investigate the effects of dietary inclusion of different levels of Rosemary and Marjoram plants ongrowth performance and digestion coefficientsof New Zealand White (NZW) rabbits.Seventy two weaned rabbits were divided into six groups. The 1 st group was fed basal diet and served as control group, the 2 nd and 3 rd groups were fed the basal diet supplementedwithRosemary dry plant powder (1.5% and 3.0%, respectively), 4 th and 5 th groups were fed the basal diet supplemented with Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In addition, Al-Jamal and Algadi (2011) reviewed that rosemary has anti-diabetic properties in terms of improving glucose utilization and oxidative metabolism of diabetic states in rats. The results of our study agreement with those reported by Hamden et al (2008) and Bakr et al (2017) they indicated that rabbits received chamomile and rosemary were significantly reduced serum glucose when compared to control group.…”
Section: Blood Constituentssupporting
confidence: 93%
“…In addition, Al-Jamal and Algadi (2011) reviewed that rosemary has anti-diabetic properties in terms of improving glucose utilization and oxidative metabolism of diabetic states in rats. The results of our study agreement with those reported by Hamden et al (2008) and Bakr et al (2017) they indicated that rabbits received chamomile and rosemary were significantly reduced serum glucose when compared to control group.…”
Section: Blood Constituentssupporting
confidence: 93%
“…The marjoram essential oil nanoemulsion (MEOE) has strong antioxidant, anti-inflammatory, and antimicrobial abilities [17]. It has considerable amounts of terpinenes (e.g., terpinen-4-ol, trans-sabinene-hydrate, γ-terpinene, α-terpinene, carvacrol, and thymol) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…MEO addition in rabbit diet alone or added to the AFB1 fed rabbits improved their BW, FI and FCR to normal values. In support, Bakr et al (2017) and Seleem et al (2007) reported enhanced final BW and WG in growing rabbits fed on diets supplemented with marjoram. Similar improved growth performance response was obtained by Ahmed and Abdel-Ghany (2015) and Ali (2014) in broiler and turkey respectively.…”
Section: Discussionmentioning
confidence: 81%
“…The enhanced performance with MEO feeding could be associated with their content of the active components (as shown in Figure 1), which was documented to have antimicrobial, antioxidant and antifungal activities (Bina and Rahimi, 2017;Kaskatepe et al, 2022). These active substances positively improved the lower gut health, enhanced the efficiency of digestion and nutrients and this reflected on rabbit growth performance (Bakr et al, 2017). In the same context, some recent studies documented the antifungal activities of essential oils of O. majorana (Amor et al, 2019;Ben Salha et al, 2019;Chaudhari et al, 2020) which accounted this effect to its contents of oxygenated monoterpenes particularly terpinen-4-ol, α-terpinol and α-pinene.…”
Section: Discussionmentioning
confidence: 93%